Utility of Soluble CD163 in the Clinical Management of Patients With Kawasaki Disease - Azuma, Yoshihiro; Suzuki, Yasuo; Okada, Seigo; Matsuguma, Chie; Wakiguchi, Hiroyuki; Ohnishi, Yuji; Furuta, Takashi; Miyake, Akiko; Yasudo, Hiroki; Ichihara, Kiyoshi; Ohga, Shouichi; Hasegawa, Shunji (Frontiers in Pediatrics, 2020)
Objective: Intravenous immunoglobulin (IVIG) therapy is a useful first-line treatment for Kawasaki disease; however, 10%-20% of patients fail to respond to this treatment. Serum levels of soluble CD163 (sCD163) are considered a biomarker for macrophage activation. There are no reports on CD163 levels in refractory Kawasaki disease. This study aimed to evaluate whether sCD163 could be a biomarker for predicting response to IVIG in Kawasaki disease. Methods: Eighty-seven patients with Kawasaki disease were enrolled in this study and classified into three groups, Group A: initial-IVIG responders, Group B: additional-IVIG responders, and Group C: patients who required other third-line therapies. Serum sCD163 levels in patients with Kawasaki disease were measured in serum samples collected before initial-IVIG treatment. The clinical and laboratory findings, including complete blood count, serum sodium, serum aspartate aminotransferase, serum alanine aminotransferase, serum C-reactive protein, and serum albumin levels, were obtained from their medical records. Results: The median (interquartile range) values of serum sCD163 levels in the three groups were as follows: Group A, 699 (478-1,072) ng/mL; Group B, 1,349 (1,116-1,390); and Group C: 665 (544-1,094). Group B showed the highest serum sCD163 levels (vs. Group A, p < 0.001, vs. Group C, p = 0.035), although the levels did not differ between Groups C and A. Conclusion: The serum sCD163 levels could be a useful biomarker for predicting the responsiveness to additional IVIG treatment in patients with Kawasaki disease.